Birth order and fluctuating asymmetry: a first look. - Lalumière, M L (1999)
We investigated the hypothesis that maternal immunoreactivity to male-specific features of the foetus can increase developmental instability. We predicted that the participants' number of older brothers would be positively related to the fluctuating asymmetry of ten bilateral morphological traits. The participants were 40 adult male psychiatric patients and 31 adult male hospital employees. Consistent with the hypothesis, the participants' number of older brothers--but not number of older sisters, younger brothers or younger sisters--was positively associated with fluctuating asymmetry. The patients had significantly larger fluctuating asymmetry scores and tended to have more older brothers than the employees, but the positive relationship between the number of older brothers and fluctuating asymmetry was observed in both groups.